Critical Study of Ayatollah Ma'refat's View on Mystical Exegesis - Rasul Mazraei (آموزه‌های قرآنی, 2021)
Scholars of the Qur'anic sciences have proposed various views on mystical interpretation. Among these thinkers is Muhammad Hadi Ma'refat. In his opinion, the documentaries (dependent) of the commentaries of the people of cognition are personal tastes and their interpretations are from the category of exegesis by opinion. Also, the meaning of the word interior which is mentioned in the narrations is a non-evident per nexum indication and also mystical interpretations are related to the association of meanings. In the present article, after collecting the data by library method, his view on mystical and esoteric exegesis has been evaluated analytically and it has been concluded that: Firstly, part of the mystics' interpretations is to express the esoteric meanings of the Qur'an and they exegete the verses and they have used common methods of understanding the text. Secondly, the exegesis of the Qur'an is not non-evident per nexum indication, but often means the inner meaning of the word of revelation and sometimes means adaptation. Thirdly, mystical exegesis is not about the association of meanings, but are references and subtleties that have entered the hearts of the people of cognition after the esoteric (internal) recitation of the Qur'an and is considered as new understanding, and in most cases there was no mental background around it to be considered with the association of meanings.